DIAGNOSTICS OF GLOMERULAR CAUSES OF HEMATURIA IN CHILDREN - A. P. Potemkina; T. V. Margieva; O. V. Komarova; P. E. Povilaitite; L. V. Leonova; T. V. Vashurina; O. I. Zrobok; A. N. Tsygin (Педиатрическая фармакология, 2012)
Hematuria is a significant manifestation, which can reflect both renal disorders and other urinary tract diseases and also be a symptom of systemic illnesses. High prevalence, diversity of etiological and trigger factors, latent course of hematuria and phenotypic resemblance of a number of underlying nephropathies symptoms cause increased interest and urgency of further investigations of such diseases features. The examination of 56 children showed that the most common cause of glomerular hematuria was hereditary kidney diseases, associated with collagen IV type mutations — 64% (Alport syndrome — 56%, thin basement membrane disease — 44%) and IgA-nephropathy — 36%. Comparative analysis of these conditions is presented in this study.